2001
DOI: 10.1093/oxfordjournals.jbchem.a002848
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Moiety of Time-Interval Measuring Enzyme Regulates Time Measurement through Its Interaction with Time-Holding Peptide PIN

Abstract: An ATPase called EA4 seems to measure time as a diapause-duration timer in the seasonal cycle of the silkworm, Bombyx mori. A peptide named PIN seems to regulate the time measurement of EA4. We characterize the EA4 as the first step to analyse its interaction with PIN. Matrix-assisted laser desorption/ionization-time of flight-mass spectrometry shows EA4 forms an equimolar complex with PIN. The binding affinity of EA4 for PIN is about 460 nM, as measured by surface plasmon resonance. Western blot analysis of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…This pro tein measures the duration of chilling required for termi nating diapause (Kai et al, 1995(Kai et al, , 1999. The time measuring function of this protein resides in its conforma tion and is triggered when a peptide "PIN" serving as "Peptidyl Inhibitory Needle" is dissociated from it (Tani et al, 2001). This system is the first elucidation of DI, at least one of its component processes, at a molecular level, although its relation to the diapause hormone (Yamashita, 1996) and the diapause-maintaining effect of polyols (Horie et al, 2000) remains to be elucidated.…”
Section: Closing Remarksmentioning
confidence: 99%
“…This pro tein measures the duration of chilling required for termi nating diapause (Kai et al, 1995(Kai et al, , 1999. The time measuring function of this protein resides in its conforma tion and is triggered when a peptide "PIN" serving as "Peptidyl Inhibitory Needle" is dissociated from it (Tani et al, 2001). This system is the first elucidation of DI, at least one of its component processes, at a molecular level, although its relation to the diapause hormone (Yamashita, 1996) and the diapause-maintaining effect of polyols (Horie et al, 2000) remains to be elucidated.…”
Section: Closing Remarksmentioning
confidence: 99%
“…This hexose is assumed to have been a mannose, but there is no evidence for this in the MS analysis. However, we have already assigned the penta-saccharide of Showa strain TIME-EA4 to branch as Man (1)(2)(3)(4)(5)(6)…”
Section: Molecular Heterogeneity Of Time-ea4mentioning
confidence: 99%
“…We have also reported that the sugar chain of TIME-EA4 was essential for its binding with the time-regulating peptide PIN. [3][4][5] It is therefore important to establish the structural background of the attaching sugar chain in relation to the TIME-EA4 timer function. We have already reported that the N-linked sugar chain of TIME-EA4 was attached at Asn 22 .…”
mentioning
confidence: 99%
See 2 more Smart Citations